The Co-create handbook - Co-create consortium
Consortium européen "Over the past 30 years, almost every aspect of doing design has changed. We still seem to be in the middle of a transition to greater entanglement and complexity, but with greater involvement of people and, hopefully, more value contributed by the design capabilities of many. We can anticipate these uncertainties with hope or fear. But if we can use design thinking, making, and enacting to visualize and explore the future together, then we will be able to harness our collective creativity to serve our collective dreams." * *Co-creation and the landscapes of design, Elizabeth B.-N. Sanders & Pieter Jan Stappers www.tandfonline.com/doi/abs/10.1080/15710880701875068
Keywords: Co-création; Europe; Idéation, dialogue et maillage